The paradox is the message Agwat-hilom (NCLA-NCCA, 2020) - Breis, Niles Jordan (2020)
Access online through this link: https://journals.upd.edu.ph/index.php/Lirip/article/view/8108/7078
Keywords: Agwat-hilom (Book); Literary magazines; COVID-19 pandemic